Skrining Kesehatan Melalui Aplikasi BPJS Serta Edukasi Tanaman Obat Keluarga (Herbal Medicine) Sebagai Upaya Kedokteran Preventif Pada Masyarakat - Ami Amelia; Arnila Melina; Delidios Arimbi; Wahyu Margi (jurnal ABDIMAS Indonesia, 2025)
Through Presidential Regulation No. 82 of 2018, concerning Health Insurance in article 48, one of the benefits of promotive preventive services is health history screening services. Health history screening abbreviated as SRK is a preventive effort that can detect participants with a potential risk of diabetes, hypertension, kidney failure and coronary heart disease. This SRK filling activity is very beneficial for JKN participants, one of which is that they can find out the potential risk of disease as early as possible for themselves and their family members. Some people still have minimal knowledge about the Mobile JKN application, there are several obstacles in the community, especially the elderly who experience either a lack of smartphones or a lack of understanding of how to use the Mobile JKN application, so these obstacles are the main problems that occur in the Marpoyan Damai area, especially in the Jl. nurul. The aim of the activity is to increase the public's insight and knowledge regarding how to use and benefit the Mobile JKN application in health history screening. In this case, the service team will provide education and assistance with health screening through the BPJS application as an effort to prevent disease. The location for this activity will be carried out in one of the neighborhoods in Pekanbaru City, namely the RT 01 RW 21 Tangkerang Tengah neighborhood, Pekanbaru City. The aim is that after this community service is carried out, it can improve the level of public health through health screening in the application and also increase the knowledge of the community in the area regarding the use of family medicinal plants (herbal medicine)